Induction Of In Plantain (Musa acuminata L.) Using The Growth Regulators 2,4-Dichlorophenoxyacetic & BAP (Benzyl Amino Purin) - Nur Fitriani, Defy; Indriati Husain; Sutrisno Hadi Purnomo (International Journal of Technology and Education Research, 2025)
Plat propagation through is a method of prodycing new plants by growing unspecified clusters (callus) from small pieces of tissue (explants) such as Gapi banana flowers. This study seeks to determine the appropriate doses of 2,4-D and BAP for callus formation. The study was conducted from September to October 2025 at the Tissue Culture Laboratory of Gorontalo State University, using male Gapi banana flowers explants. The experiment used a randomized block design (RBD) involving two factors: 2,4-D (2ppm) and BAP (5, 10, 15 ppm). The percentage of live explants (%) was observed weekly for 30 days. Final observation included browning, The results showed that the addition of 2,4-D and BAP to the medium greatly affected the percentage of live explants. Without these substances, the explants turned brown. Fungal contamination was dominant at D0 (control) and D2 (2 ppm 2,4-D + 10 ppm BAP). The callus was white/cream to greenish in color, with a firm texture. The percentage of callus-forming explants (%) increased with the addition of BAP (5, 10 and 15ppm), significantly affecting callus formation.